PENGARUH WORD OF MOUTH (WOM) TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DI KAMPUNG ADAT BOTI KABUPATEN TTS - Janet I Paulus; Juita L. D Bessie; Abas Kasim (Universitas Nusa Cendana, 2015)
This research aims to determine the effect of word of mouth (WOM) simultaneously and partiallyon tourist’s visiting decisions in the Village of Indigenous Boti in TTS district. The independentvariables were examined are Volume and Dispersion. The samples in this research are 60respondents, collected using accidental sampling technique. The research used questionnaire asresearch instrument and analyzed with multiple regression analysis. From regression analysisobtained the equetion as follows : From the classic assumption test, regression models are independent and normaly distributed. Y = 3,142 + 0,578X1 + 0,560X2Hypotesis testing using t test known that variables Volume and Dispersion partially influence thetourist’s visiting decision variable significantly. Then through the F test seen that Volume andDispersion variables simultaneously influence the tourist’s visiting decision variable significantly.The value of adjusted R square is 0,507 which is mean that 50,7% of the decisions being influencedby Volume and Dispersion variables. While the remaining 49.3% of the decision influenced byother variables which is not examined. Keywords: Word of Mouth (Volume and Dispersion), Tourist’s Visiting Decision